1994
DOI: 10.1063/1.467487
|View full text |Cite
|
Sign up to set email alerts
|

Phase transitions in mixed Langmuir films of 8CB and stearic acid

Abstract: Articles you may be interested inAnalysis of linear and quadratic optical response of mixed Langmuir-Blodgett films of stearic acid and 5-CT Effects of surface tension of substrate on annealing of evaporated stearic acid film

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 26 publications
3
10
0
Order By: Relevance
“…72 The linear and nonlinear optical properties of the nCB films have been extensively studied as model systems for understanding of the structure and phase transitions of the LCs with theoretical importance and potential technological use. [73][74][75][76] Studies on the structure and film stability of the nCB and nCT monolayers, and the binary monolayers with a mixture of the nCB or the nCT with other surface active molecules at the air/water interface have also been pursued using surface second harmonic generation (SHG) techniques 7,77,78 and surface pressure and Brewster angle microscopy (BAM). 7,[63][64][65][66][67][68][69][70][71] The phase diagram and phase behaviour of the 8CB or 5CB and the 5CT Langmuir monolayes are significantly different.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…72 The linear and nonlinear optical properties of the nCB films have been extensively studied as model systems for understanding of the structure and phase transitions of the LCs with theoretical importance and potential technological use. [73][74][75][76] Studies on the structure and film stability of the nCB and nCT monolayers, and the binary monolayers with a mixture of the nCB or the nCT with other surface active molecules at the air/water interface have also been pursued using surface second harmonic generation (SHG) techniques 7,77,78 and surface pressure and Brewster angle microscopy (BAM). 7,[63][64][65][66][67][68][69][70][71] The phase diagram and phase behaviour of the 8CB or 5CB and the 5CT Langmuir monolayes are significantly different.…”
Section: Resultsmentioning
confidence: 99%
“…The molecular detail of the orientational order of the 8CB Langmuir monolayer before and after the transition between Regions I and II was quantitatively analyzed with a surface second harmonic generation (SHG) measurement in different polarization combinations. 58,77 It was found that a continuous orientational distribution narrowing (ODIN) process started before Region II and ended at just the transition point of the surface pressure, where a closely packed homogeneous monolayer was finally formed to give a steep rise of the surface pressure under further compression. 58 Using BAM, Inglot and co-workers studied the nCB Langmuir monolayers and found that for 4 r n r 12 their phase diagram and phase behaviour were both similar to those of the 8CB monolayer.…”
Section: Resultsmentioning
confidence: 99%
“…The components of the dielectric tensor then follow from ε ∥ = = 2.86 and ε ⊥ = = 2.34. We also set φ equal to 71° and the monolayer thickness (to which the results are not very sensitive) d 1 to 1.2 nm. Computed images of the splay−bend structure 27 of the defects in the 10CB monolayers were generated for a range of values of ε x ‘ , which is related to ε y ‘ through eq 16.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…A number of papers have described the application of SHG for studies of the tilt angle of 8CB and related molecules in monolayers including Langmuir films at the air/water interface. In most cases, a simplified analysis has been used in which it is assumed that β zzz is the only nonzero element of β (2) . In the simplified analysis, the ratio of susceptibility elements χ ZXX /χ ZZZ is obtained from measurements of SHG using selected plane-polarized states of fundamental and second harmonic radiation. ,, The tilt angle, θ o , of the chromophore relative to the surface normal, Z , is then obtained by using eq 2.…”
Section: Introductionmentioning
confidence: 99%